Cathelicidin regulates myeloid cell accumulation in adipose tissue and promotes insulin resistance during obesity - Braster, Quinte; Silvestre-Roig, Carlos; Hartwig, Helene; Kusters, Pascal; Aarts, Suzanne; den Toom, Myrthe; Gallo, Richard L.; Weber, Christian; Lutgens, Esther; Soehnlein, Oliver (Thrombosis and Haemostasis, 2016)
Note: The review process for this manuscript was fully handled by Gregory Y. H. Lip, Editor in Chief.